2016
DOI: 10.4103/1319-2442.178259
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the quality of life of the patients undergoing hemodialysis versus peritoneal dialysis and its correlation to the quality of dialysis

Abstract: Over the years, there has been a steady increase in the number of patients requiring dialysis. However, no consensus exists between choosing either hemodialysis (HD) or peritoneal dialysis (PD) as the preferred method of dialysis for patients. In this study, we have compared the quality of life of the patients undergoing either HD or PD. This cross-sectional study was performed in the dialysis center of the Noor and Saint Ali Asghar University Hospital in Isfahan, Iran in 2012. Forty-six patients who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 1 publication
0
13
2
3
Order By: Relevance
“…A total of 46 articles was eligible for critical appraisal. 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 The following articles presented overlapping patient data and were appraised as one: Bujang et al 91 and Liu et al, 92 Chkhotua et al 94 and Maglakelidze et al, 95 Griva et al 103 and Yang et al, 104 2 articles by Kontodimopoulos 111 , 112 and 2 articles by Theofilou, 120 , 121 leaving 41 studies for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 46 articles was eligible for critical appraisal. 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 The following articles presented overlapping patient data and were appraised as one: Bujang et al 91 and Liu et al, 92 Chkhotua et al 94 and Maglakelidze et al, 95 Griva et al 103 and Yang et al, 104 2 articles by Kontodimopoulos 111 , 112 and 2 articles by Theofilou, 120 , 121 leaving 41 studies for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Atapour et al found no relation between duration on hemodialysis and QOL in patients with CKD. 24 It is interesting to note that ethnicity affected the overall perception of general health in the patients undergoing hemodialysis. Terai/Madhesi ethnic group had lower scores in this dimension than other groups.…”
mentioning
confidence: 99%
“…19 Many authors from different regions compared hemodialysis and peritoneal dialysis patients and were of the opinion that PD improved quality of life. 20 On the contrary one south African study observed higher symptom burden in PD patients compared to hemodialysis. 21 A systematic review comparing both treatment modalities was also inconclusive on the benefit of PD.…”
Section: Discussionmentioning
confidence: 95%